Tomato brown rugose fruit virus: An emerging and rapidly spreading plant RNA virus that threatens tomato production worldwide. (22nd May 2022) - Zhang, Shaokang; Griffiths, Jonathan S.; Marchand, Geneviève; Bernards, Mark A.; Wang, Aiming
Abstract: Tomato brown rugose fruit virus (ToBRFV) is an emerging and rapidly spreading RNA virus that infects tomato and pepper, with tomato as the primary host. The virus causes severe crop losses and threatens tomato production worldwide. ToBRFV was discovered in greenhouse tomato plants grown in Jordan in spring 2015 and its first outbreak was traced back to 2014 in Israel. To date, the virus has been reported in at least 35 countries across four continents in the world. ToBRFV is transmitted mainly via contaminated seeds and mechanical contact (such as through standard horticultural practices). Given the global nature of the seed production and distribution chain, and ToBRFV's seed transmissibility, the extent of its spread is probably more severe than has been disclosed. ToBRFV can break down genetic resistance to tobamoviruses conferred by R genes Tm‐1, Tm‐2, and Tm‐2 2 in tomato and L 1 and L 2 alleles in pepper. Currently, no commercial ToBRFV‐resistant tomato cultivars are available. Integrated pest management‐based measures such as rotation, eradication of infected plants, disinfection of seeds, and chemical treatment of contaminated greenhouses have achieved very limited success. The generation and application of attenuated variants may be a fast and effective approach to protect greenhouse tomato against ToBRFV. Long‐term sustainable control will rely on the development of novel genetic resistance and resistant cultivars, which represents the most effective and environment‐friendly strategy for pathogen control. Taxonomy: Tomato brown rugose fruit virus belongs to the genus Tobamovirus, in the family Virgaviridae . The genus also includes several economically important viruses such as Tobacco mosaic virus and Tomato mosaic virus . Genome and virion: The ToBRFV genome is a single‐stranded, positive‐sense RNA of approximately 6.4 kb, encoding four open reading frames. The viral genomic RNA is encapsidated into virions that are rod‐shaped and about 300 nm long and 18 nm in diameter. Tobamovirus virions are considered extremely stable and can survive in plant debris or on seed surfaces for long periods of time. Disease symptoms: Leaves, particularly young leaves, of tomato plants infected by ToBRFV exhibit mild to severe mosaic symptoms with dark green bulges, narrowness, and deformation. The peduncles and calyces often become necrotic and fail to produce fruit. Yellow blotches, brown or black spots, and rugose wrinkles appear on tomato fruits. In pepper plants, ToBRFV infection results in puckering and yellow mottling on leaves with stunted growth of young seedlings and small yellow to brown rugose dots and necrotic blotches on fruits. Abstract : This pathogen profile summarizes current knowledge about ToBRFV, highlights recent research progress, discusses future research directions, and proposes short‐run and long‐term control strategies.